Effect of moisture content on collapsibility rate at Gambang residual soil - Mohd Haffizul Said, Mohd Ramdzan (2009)
Residual soil is a material formed in situ by weathering of rock and remained at the place where it was formed. In Malaysia, residual soil covers more than 80% of the country land area. This type of soil has high possibility to collapse when raining or wetted. The objectives of this study are to determine the collapsibility rate of soil at Gambang and to determine the factors that cause collapsibility and the effect of wet soil on the collapsibility. Gambang has been choose as the case study because of the topography of the land is hilly and this place has a history of land slide, there is also a slop that is not covered by plan and it seems that the slope crack during the sunny day and if the rain comes, the soil will wetted and collapse. One-Dimensional consolidation test or oedometer test is carried out to test the soil sample. From the result obtained, the soil is found with collapse possibility because of the quantity of the void ratio is high and the soil has low shear strength. The soil collapsibility rate is found high after the test has been conducted.